2004
DOI: 10.2337/diacare.27.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity and Body Composition as Predictors of Mortality Among Men With Diabetes

Abstract: OBJECTIVE -To quantify the relation of fitness to mortality among men with diabetes, adjusted for BMI and within levels of BMI.RESEARCH DESIGN AND METHODS -In this observational cohort study, we calculated all-cause death rates in men with diabetes across quartiles of fitness and BMI categories. Study participants were 2,196 men with diabetes (average age 49.3 years, SD 9.5) who underwent a medical examination, including a maximal exercise test, during 1970 to 1995, with mortality follow-up to 31 December 1996… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
271
2
9

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 410 publications
(304 citation statements)
references
References 18 publications
22
271
2
9
Order By: Relevance
“…Results of other prospective studies in men and women further suggest that high levels of physical activity protect against the incidence of coronary artery disease, independent of BMI, as well as other factors such as age, smoking, diabetes and hypertension (62). Furthermore, prospective analyses from the Aerobics Center Longitudinal Study have consistently reported that CRF is a significant predictor of mortality from all causes (9,10,63,64), CVD (9,10) and type 2 diabetes (65) in men and women, independent of BMI or WC. These relationships have been confirmed in older adults (66) and Canadian women (67).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 88%
“…Results of other prospective studies in men and women further suggest that high levels of physical activity protect against the incidence of coronary artery disease, independent of BMI, as well as other factors such as age, smoking, diabetes and hypertension (62). Furthermore, prospective analyses from the Aerobics Center Longitudinal Study have consistently reported that CRF is a significant predictor of mortality from all causes (9,10,63,64), CVD (9,10) and type 2 diabetes (65) in men and women, independent of BMI or WC. These relationships have been confirmed in older adults (66) and Canadian women (67).…”
Section: Exercise-induced Reduction In Cardiometabolic Risk Factors Wmentioning
confidence: 88%
“…In addition, regular exercise training has strong and independent cardioprotective effects, leading to lower cardiovascular morbidity and mortality in type 2 diabetes (Church et al 2004). These effects of exercise training may, at least partly, be mediated through the direct effect of exercise on the arterial wall Joyner and Green 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise also enhances skeletal muscles, cardiopulmonary function, and psychological health; these benefits cannot be achieved by pharmacotherapy or dietary changes 6,7) . In diabetic patients, enhanced cardiopulmonary function because of exercise has been linked with prolonged life 8) . The benefits of exercise in the prevention of diabetes are well known 9,10) .…”
Section: Introductionmentioning
confidence: 99%